2019
DOI: 10.1021/acs.macromol.9b01325
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic Emission Tuning of Carborane-Containing Poly(dihexylfluorene)s

Abstract: Incorporation of o-carborane into the backbone of poly­(dihexylfluorene)­s drastically affects emission properties due to an intramolecular charge-transfer state (ICT) that forms between the fluorene and carborane moieties in the polymer backbone, which is emissive and solvatochromic. Such polymers exhibit duel emissions from both the ICT state and the conjugated fluorene local excited state (LES). In order to evaluate the influence of higher degrees of LES conjugation on the emission properties of carborane-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 55 publications
(84 reference statements)
0
24
0
Order By: Relevance
“…Given the previous reports on the improved emissive behavior of carborane‐fluorophore conjugates upon aggregation, [6,7c–j] we also investigated the optical properties of 1 and 2 in the solid state, which were compared to those of reference PDI dye 7 . As previously reported for thin films of symmetric perylenediimide fluorophores bearing branched alkyl side chains, [37] large differences were observed when optically characterizing 7 as a solid powder relative to solution.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the previous reports on the improved emissive behavior of carborane‐fluorophore conjugates upon aggregation, [6,7c–j] we also investigated the optical properties of 1 and 2 in the solid state, which were compared to those of reference PDI dye 7 . As previously reported for thin films of symmetric perylenediimide fluorophores bearing branched alkyl side chains, [37] large differences were observed when optically characterizing 7 as a solid powder relative to solution.…”
Section: Resultsmentioning
confidence: 99%
“…The emission from these AIE‐active, CT‐based carborane‐emitter conjugates is sensitive to external stimuli that alter molecular packing (e.g. mechanical forces, temperature, chemical environment), and can be used for the preparation of smart materials [7c–j] . However, attempts to provide further functionality to these systems by reversibly switching the electronic communication between fluorophores and boron clusters have not been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Carter et al. reported a series of carborane‐containing polyfluorenes 25 – 27 . Optoelectronic devices were fabricated with the emissive conjugated network involving o ‐carborane for the first time.…”
Section: Aggregation‐induced Emissionmentioning
confidence: 99%
“…It was demonstrated that the carborane cage is responsible for the improvement of charge carrier mobility by an order of magnitude . In another paper, the emission color was tuned in a wide wavelength range by changing the introduction rate of the carborane unit . Moreover, 25 showed vapochromic properties.…”
Section: Aggregation‐induced Emissionmentioning
confidence: 99%
“…Owing to these features, such o -carboranyl compounds have recently been proposed as promising optoelectronic materials for organic light emitting diodes [ 7 , 8 ] and organic thin-film transistors [ 9 , 10 ]. The intriguing photophysical properties of o -carboranyl luminophores originate from the electronic donor‒acceptor (D–A) dyad formed by combining a π-conjugated aromatic organic fluorophore (donor) with an o -carborane (acceptor) [ 4 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 ]. The strong electron-withdrawing ability of the carbon atoms in the o -carborane cage, which is derived from the high polarizability of the σ-aromaticity [ 37 , 38 , 39 , 40 , 41 ], allows this moiety to act as an electron acceptor during external excitation and relaxation processes.…”
Section: Introductionmentioning
confidence: 99%